A fatal accidental subarachnoid injection of lidocaine and levobupivacaine during a lumbar paravertebral block. (November 2015) - Busardò, Francesco Paolo; Tritapepe, Luigi; Montana, Angelo; Indorato, Francesca; Zaami, Simona; Romano, Guido
Highlights: A fatal case involving a 60-year-old woman who underwent paravertebral block. The physician unintentionally performed a subarachnoid injection (L5-S1bilaterally). Lidocaine and bupivacaine were detected by GC–MS in blood, CSF and urine. The cause of death was due to a progressive hypotension and normovolaemic shock. Abstract: Paravertebral block (PVB) is the technique of injecting a local anesthetic solution alongside the vertebral column, close to where the spinal nerves emerge, resulting in unilateral somatic and sympathetic nerve blockade. Here is reported a fatal case involving a 60-year-old woman with spondylitis arthropathy, who developed cardiac and respiratory arrest 40 min after receiving an accidental subarachnoid injection (L5-S1 bilaterally) of depomedrol lidocaine and levobupivacaine. A complete autopsy including histological and toxicological analyses was performed in order to establish the cause of death. Liquid/liquid extraction (LLE) and GC–MS analysis were performed according to a previously published method. Lidocaine and bupivacaine were detected both in blood, at concentrations of 14.8 mg/L and 13.3 mg/L respectively, and in cerebrospinal fluid (CSF) at concentrations of 287.1 mg/L and 464.2 mg/L respectively. Both lidocaine and bupivacaine were also detected in the urine. The toxicological findings along with the autopsy allowed us to establish that the accidental subarachnoid injection of lidocaine and levobupivacaine had led to a progressive hypotension and normovolaemic shock caused by a severe ganglionic block, determining the patient's death.